Beneath the crust of culture : psychoanalytic anthropology and the cultural unconscious in American life - Stein, Howard F. (Amsterdam ; New York : Rodopi, 2004)
In this book, the author presents a pioneering interpretation of culture as constituting a dynamic relationship between the visible "crust" and the elusive "core" of social life. He meticulously maps the role of the unconscious in shaping much of American life in the late 20th and early 21st centuries. He crosses and transcends disciplinary boundaries in studies of September 11, 2001, the 1999 Columbine High School massacre, the execution of Timothy McVeigh, the 1995 Oklahoma City bombing, the 1999 Worcester, Massachusetts fire, and the eruption of hypernationalism and xenophobia in nations and workplaces - all as cultural phenomena with a psychodynamic core. He shows how the experience of loss in the face of massive social change often leads to equally massive defence against the experience of mourning. Beneath the Crust of Culture will be of interest not only for behavioural and social science professionals, but also for a lay public interested in understandings of culture deeper than the surface of the news and of official pronouncements
FOREWORD by Jon Mills -- PREFACE -- ACKNOWLEDGMENTS -- ONE: Days of Awe: September 11, 2001 and Its Cultural Psychodynamics -- TWO: Disposable Youth: The 1999 Columbine High School Massacre as American Metaphor -- THREE: The Execution of Timothy McVeigh: Cultural Mystification and Deeper Clues -- FOUR: Hypernationalism and Xenophobia in Workplace and Nation State -- FIVE: The Left Out and the Forgotten: An Approach to Understanding Disasters -- SIX: Mourning and Society: Situating Loss and Grief in the History and Philosophy of Science -- EPILOGUE -- ABOUT THE AUTHOR -- REFERENCES -- INDEX.
Includes bibliographical references (pages 125-134) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Ethnopsychology -- United States; United States -- Civilization -- 1970- -- Psychological aspects; Ethnology; Psychoanalysis; Social psychology; Subconsciousness; Anthropology, Cultural; Ethnopsychology; Psychoanalytic Theory; Psychology, Social; Unconscious, Psychology; Violence -- psychology; United States; Ethnopsychologie -- États-Unis.; États-Unis -- Civilisation -- 1970- -- Aspect psychologique; Ethnologie; Psychanalyse; Psychologie sociale; Inconscient; psychoanalysis; social psychology; unconscious; PSYCHOLOGY -- Ethnopsychology; Subconsciousness; Social psychology; Psychoanalysis; Ethnology; Civilization -- Psychological aspects; Ethnopsychology; United States; Since 1970